CLUSTER MECHANISMS OF WORKING WITH CHILDREN WITH AUTISM SYNDROME IN THE ENVIRONMENT OF STUDENTS WITH SPECIAL EDUCATION NEEDS (Scientific journal of the Fergana State University, 2024)
The article presents theoretical and practical aspects of the organization of education of children with autism syndrome in the system of inclusive education. At the same time, the communication skills of students with autism syndrome are being studied. The literature is analyzed, on the basis of which the main features of the violation of communicative abilities in schoolchildren with autism syndrome are revealed. In the context of inclusive education, the problems of students with autism syndrome were generalized and identified.